Implementation of Group Learning Strategies to Improve the Academic Performance of Grade XI Social Science Students at MAPN Medan - Ananta, Muhammad Afif (Kitabah: Jurnal Pendidikan Sosial Humaniora, 2026)
This study aims to analyze the effectiveness of implementing group learning strategies to improve the academic performance of Grade XI Social Science students at MAPN Medan. The background of the study arises from the low level of student engagement and collaborative skills within traditional learning settings. A quantitative approach using a quasi-experimental design was employed, involving an experimental class implementing group learning strategies and a control class using conventional lecture-based methods. Research instruments included achievement tests and student activity observation sheets. The findings reveal a significant improvement in the academic performance of students in the experimental class compared with those in the control class. Students also demonstrated enhanced learning engagement, communication skills, and cooperation throughout the learning process. These results indicate that group learning strategies are effective in improving student learning outcomes and academic performance. The study recommends applying similar strategies in other learning contexts to support more active, collaborative, and meaningful learning experiences.